Obama's road to Cairo: The president's rhetorical journey, 2008-2009 - Nils E. Lukacs (German Institute of Global and Area Studies (GIGA), 2019)
Ten years ago, President Barack Obama's unprecedented address to the Muslim world from Cairo was hailed as a landmark in US-Middle Eastern relations and described by contemporary observers as a historical break in US foreign policy in the region. Yet it soon became clear that the president's vision for a "new beginning based on mutual interest and mutual respect" would face many practical constraints. Analysing the thematic and rhetorical development of Obama's speeches during the formative period between summer 2008 and 2009, as well as the public and academic perception of and reaction to these moments, the paper examines the underlying interests and motivations for the president's foreign policy approach in the Middle East. It argues that despite the low priority given to foreign policy issues during the economic crisis occurring at the time, the key pillars of Obama's ambitious vision for the Middle East were rooted in pronounced US interests as well as the president's personal convictions, rather than opportunistic calculations. It thus counters retrospective post-2011 criticism which argues that Obama's words were never meant to be put into practice. The study contributes to the establishment of a solid empirical and conceptual base for further research on the United States' foreign policy in the Middle East under the Obama administration.
Keywords: 300; US foreign policy; Barack Obama; Middle East; New Beginning; Cairo; rhetoric